OPTIMALISASI PENERAPAN AKAD MUDHARABAH DALAM KONTEKS LEMBAGA KEUANGAN SYARIAH - Wardatul Wahidah. R; Rahayu Japar; Yusri Karmila; Rahman Ambo Masse (Jurnal Teknologi Pendidikan Madrasah, 2024)
The research title is about the Implementation of Mudharabah Agreements in Sharia Financial Institutions. This type of descriptive or exploratory research describes and explains the implementation of mudharabah contracts in sharia financial institutions using a qualitative research approach. In this research, the Library Research method (library study) is used, the data sources come from official documents such as books and journals. The results obtained in this research explain that financing or the process of borrowing capital or providing capital is one of the sharia banking facilities that really helps customers. One of the interesting things is financing with the Mudharabah scheme. Mudharabah can be interpreted as a business cooperation agreement between two parties. The two parties are the fund owner as the first party who provides all the funds (100%) and the fund manager as the second party who acts as manager. In Mudharabah, business profits are shared according to the agreement of all parties written in the contract agreement. Then, if you experience a financial loss, the first party will bear it, but if it is due to the manager's negligence, it will be borne by the fund manager. The value of justice in a Mudharabah contract lies in the benefits and risk sharing of each party who is collaborating according to the portion of their involvement. The aim of this research is to determine the application of mudharabah financing, the principles of sharing business results and the application of justice in mudharabah financing in sharia banking.